An update on road traffic injuries in Malaysia - Krishnan, R.; Sohadi, Radin Umar Radin (Faculty of Medicine, University of Malaya, 1997)
The incidence of road traffic injuries has increased over the last two decades. Of greater concern is the prediction that the problem is likely to increase further, given present trends in transportation. Injuries and not "accidents" need to be the focus of the health sector. Passive strategies, which are independent of human behavior, are more likely to succeed in the prevention of injuries compared to ''active' strategies. The health sector needs to play a bigger role in prevention through advocacy, research and education of target groups.